Terrorism Phenomenon in Indonesia: Study of Theological Aspects, Ideology and Movement - Arnovan Pratama Surbakti; Yasmirah Mandasari Saragih; Muhammad Azhali Siregar; Ryan Fadli Siregar (International Journal of Law, Crime and Justice, 2024)
Terrorism is a theme that invites the attention of many in the academics to examine the main aspects of ideology, theology, networks and movements. At this time, terrorism has become a global phenomenon. Terrorism has penetrated almost every country in the world, including Indonesia. As in other areas, terrorism in Indonesia also has the basics of theology and ideology and networks so that it has a strong resistance. Until recently, terrorism became one of the challenges and threats to national security. This article is to examine the development of terrorism in Indonesia, which focuses on aspects of theology, ideology and movement.